Steps towards an integrated view of nitrogen metabolism - Stitt, Mark (Journal of experimental botany, 2002)
This article discusses how nitrate assimilation is integrated with nitrate uptake, with ammonium assimilation and amino acid synthesis, with pH regulation, and with the sugar supply in tobacco leaves. During the first part of the light period, nitrate assimilation exceeds nitrate uptake by 2-fold and ammonium assimilation by 50%, leading to rapid depletion of nitrate and accumulation of ammonium, glutamine, glycine and serine. NIA, NII and PPC expression show a shared maximum early in the diurnal cycle to direct carbon towards malate synthesis for pH regulation. Later in the diurnal cycle an orchestrated increase of GLN2, PKc, CS, and ICDH-1 expression re-establishes a balance between nitrate assimilation and ammonium metabolism. Nitrate uptake continues throughout the night, replenishing the leaf nitrate pool. These diurnal changes are attenuated or abolished in mutants with low NIA activity, and modified in wild-type plants growing on different nitrogen sources or elevated [CO(2)]. Comparison across genotypes and conditions reveals that NIA transcript levels are always closely related to the balance between nitrate influx and assimilation, but are unrelated to changes of glutamine or 2-oxoglutarate. In a systematic search for other downstream regulators, a wide range of downstream metabolites was fed to detached leaves and glutamate, cysteine, asparagine, and malate identified as candidates. Low sugars totally inhibit nitrate assimilation, overriding signals from nitrogen metabolism. Moderate changes act post-transcriptionally, and larger changes lead to a collapse of the NIA transcript. Low sugars also lead to a collapse of minor amino acids and a dramatic decrease of phenylpropanoids and nicotine. Consequently, wild-type plants growing in unfavourable light regimes and antisense RBCS transformants are simultaneously carbon- and nitrogen-limited